Cutting teeth ebook A novel. - Baker, Chandler (2023)
THE NATIONAL BESTSELLER "Jaw-dropping ... A darkly comic send-up of motherhood." — People "With devourable writing and pitch-perfect humor, Cutting Teeth is a sharp, original, wickedly astute look at the sting of modern motherhood." —Ashley Audrain, New York Times bestselling author of The Push New York Times bestselling author Chandler Baker's Cutting Teeth is a witty, thrilling story of parental love that asks: is there anything a mother won't do for her children? Darby, Mary Beth, and Rhea are on personal quests to reclaim aspects of their identities subsumed by motherhood—their careers, their sex lives, their bodies. But their children disrupt their plans when an unsettling medical condition begins to go around the Little Academy preschool: the kids are craving blood. Then a young teacher is found dead, and the only potential witnesses are ten adorable four-year-olds. Soon it becomes clear that the children are not just witnesses, but also suspects . . . and so are their mothers. As the police begin to look more closely, the children's ability to bleed their parents dry becomes deadly serious. Part murder mystery, part motherhood manifesto, Cutting Teeth explores the standards society holds mothers to—along with the ones to which we hold ourselves—and the things no one tells you about becoming a parent.